The Relationship Between Tutor Interpersonal Communication and Learning Outcomes in Mathematics Package C at the Sepakat Bersama Community Learning Center (PKBM) in Padang - Tamara, Adila; 'Aini, Wirdatul (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research is motivated by the low learning outcomes of mathematics subjects of package C learners atPKBM Sepakat Bersama, Padang City. The objectives of this study are to describe: (1) tutor interpersonalcommunication, (2) mathematics learning outcomes, and (3) the relationship between tutor interpersonalcommunication and learning outcomes of package C mathematics subjects at PKBM Sepakat Bersama, PadangCity. This study uses a quantitative method with a correlational type. The population in this study werelearners who took package C equivalency education at PKBM Sepakat Bersama, Padang City, totaling 45people. Meanwhile, the research sample was taken using a stratified random sampling technique so that thenumber of samples obtained for this study was 70% of the total population, namely 33 people. Questionnairesthat had passed validity and reliability tests were used to collect data, then analyzed using percentage analysisand Product Moment correlation techniques. The research findings show that (1) Tutor interpersonalcommunication is considered less good, (2) The learning outcomes of package C learners in mathematics arelow, and (3) There is a significant relationship between tutor interpersonal communication and learningoutcomes of package C mathematics subjects at PKBM Sepakat Bersama, Padang City.Keywords: Tutor Interpersonal Communication, Learning Outcomes, Community Service Program (PKBM)